Uma nova configuração de sistemas de acionamento: conexão retificador-inversor através de cabos longos - análise da economia de cobre e da proteção do sistema contra faltas - Joao Americo de Castro Junior (2010)
Problems involving long cable PWM motor drive systems are well documented in the literature. Solutions based on passive filters are traditionally used to suppress the undesired high-frequency phenomena that take place in such systems, but, in turn, bring up new considerations concerning filter size, weight, cost and electrical losses. In this context, the concept of an alternative motor drive system that overcome all these problems is outlined in this work, where the long cable is used to connect the rectifier to the inverter, thus establishing a DC power transmission link. Another important advantage of such system is the lower amount of copper required for the power transmission in comparison to the traditional configuration, whose accurate calculation is the main goal of the present work. A study concerning important issues regarding the system protection against faults within the DC link is also presented.